Las técnicas grafo-plásticas y su relación con el aprendizaje de las niñas y niños de preparatoria, primer grado de la escuela de educación básica “José María Urbina”, de la parroquia San Pedro de los Cofanes, cantón Shushufindi, provincia de Sucumbíos. Período lectivo 2013-2014 - Linares Ruales, Dora Nohemí (2014)
This thesis refers to "THE GRAPH-PLASTIC TECHNICAL AND ITS RELATIONSHIP WITH LEARNING GIRLS AND BOYS HIGH SCHOOL, FIRST GRADE SCHOOL OF BASIC EDUCATION" JOSE MARIA URBINA "PARISH OF SAN PEDRO KOFAN, CANTON SHUSHUFINDI, SUCUMBÍOS PROVINCE. LECTIVO PERIOD 2013-2014 " It was conducted according to the provisions of the Regulation of Academic Board of the National University of Loja. Raised as General Objective: Analyze the Graph-It Plastic Techniques and its relationship to learning for girls and boys High School, First Grade, School of Basic Education "José María Urbina". The methods used for the preparation of this research work were: Scientist, Inductive-Deductive, Analytic-Synthetic and Statistical Model, which served them help efficiently achieve the goal. The techniques and instruments used were: Survey applied to Parents of High School children, First Grade, School of Basic Education "José María Urbina" in order to determine the structure and functionality of their homes Family Observation Checklist and the same for girls and boys High School, First Grade, School of Basic Education "José María Urbina" was applied to evaluate the learning. It is concluded that: 67% of teachers surveyed used in the daily work with children Graph-visual techniques as dactyl-painting and bucking; 33% torn, crushed and modeling. Techniques Graph-plastic are used to support the development of children in aspects of thinking, oral and written language, creativity, socialization, a better understanding of himself and others, helps develop all areas of the child, leading to the stimulation of the senses and the imagination. The results of the observation guide determine that: 62% of girls and children observed have an equivalent learning Very Satisfactory, 29% and 9% Satisfactory Unsatisfactory. Learning is the diversity of activities that the children according to their abilities and skills where prior knowledge and experience interact to get a score based on changes in their behavior regarding the psychomotor, affective, social, evolutionary and intellectual.